2006
DOI: 10.1073/pnas.0605180103
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic brain-derived neurotrophic factor expression causes both anxiogenic and antidepressant effects

Abstract: Although neurotrophins have been postulated to have antidepressant properties, their effect on anxiety is not clear. We find that transgenic overexpression of the neurotrophin BDNF has an unexpected facilitatory effect on anxiety-like behavior, concomitant with increased spinogenesis in the basolateral amygdala. Moreover, anxiogenesis and amygdalar spinogenesis are also triggered by chronic stress in control mice but are occluded by BDNF overexpression, thereby suggesting a role for BDNF signaling in stressind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
244
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(277 citation statements)
references
References 46 publications
25
244
1
3
Order By: Relevance
“…The current behavioral data are consistent with results showing that in male Sprague-Dawley rats, a bilateral infusion of BDNF (0.25 and 1.0 mg) into the dentate gyrus of the hippocampus increases the swimming behavior in the FST and, therefore produces antidepressant-like phenotype (Shirayama et al, 2002). In addition, Govindarajan and coworkers reported that genetically modified mice overexpressing BDNF in excitatory neurons of the forebrain, including the hippocampus, displayed improved performance in the Porsolt FST (Govindarajan et al, 2006). In contrast, heterozygous (+/À) BDNF mice were resistant to the effects of antidepressants in the FST, indicating that antidepressantinduced behavioral effects require regular BDNF signaling (Lindholm et al, 2012;Saarelainen et al, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…The current behavioral data are consistent with results showing that in male Sprague-Dawley rats, a bilateral infusion of BDNF (0.25 and 1.0 mg) into the dentate gyrus of the hippocampus increases the swimming behavior in the FST and, therefore produces antidepressant-like phenotype (Shirayama et al, 2002). In addition, Govindarajan and coworkers reported that genetically modified mice overexpressing BDNF in excitatory neurons of the forebrain, including the hippocampus, displayed improved performance in the Porsolt FST (Govindarajan et al, 2006). In contrast, heterozygous (+/À) BDNF mice were resistant to the effects of antidepressants in the FST, indicating that antidepressantinduced behavioral effects require regular BDNF signaling (Lindholm et al, 2012;Saarelainen et al, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…Govindarajan et al 78 reports that mice genetically modified to overexpress BDNF exhibit increased anxiety-like behaviour as well as an increase in spinogenesis of the basolateral amygdala, comparable to that seen in wild-type mice exposed to chronic immobilization stress. Furthermore, the same stress protocol was unable to exacerbate the cellular abnormalities in the transgenic mice, suggesting a role for BDNF in stress-induced plasticity of the amygdala.…”
Section: Can Genetically Altered Mice Help?mentioning
confidence: 95%
“…If this is true, these results would provide additional evidence against a causal relationship between reduced brain BDNF levels and depression. However, Govindarajan et al 78 also report that overexpression of BDNF was able to protect mice from stress-induced atrophy of Table 3 Evidence for and against the BDNF hypothesis of depression from studies using genetically altered mice…”
Section: Can Genetically Altered Mice Help?mentioning
confidence: 99%
“…They also showed a slight but significant increase in hippocampal neurogenesis. The behavioral pattern of the anxiogenic-like effect and reduced immobility in the FST observed in PDE4BÀ/À mice appears not uncommon; it also occurs in BDNF transgenic mice (Govindarajan et al, 2006) and in rats treated acutely with pentylenetetrazol (Cannizzaro et al, 1993) or fluoxetine (Zienowicz et al, 2006). Thus, the present data suggest that PDE4B plays a role in the anxiogenic-like effects of acute rolipram (Heaslip and Evans, 1995;Imaizumi et al, 1994), which also exerts antidepressant activity.…”
Section: Pde4b-deficiency and Behavior H-t Zhang Et Almentioning
confidence: 99%